PREVALENCE OF AFB POSITIVITY AMONG INPATIENTS IN THE INFECTIOUS DISEASE DEPARTMENT AT TRA VINH GENERAL HOSPITAL (Tạp chí Y học Cộng đồng, 2026)
Objectives: To determine the rate of acid-fast bacilli (AFB)-positive results and associated factors among inpatients with AFB test orders in the Infectious Disease Department of Tra Vinh General Hospital from January to September 2023.Methods: A cross-sectional descriptive study combined with retrospective data collection was conducted on 157 inpatients who had AFB sputum smear tests ordered from the Infectious Disease Department. Data were collected from medical records, laboratory results, and structured questionnaires. AFB smears were performed using the Ziehl-Neelsen staining method. Statistical analysis was conducted using Stata 14.0; Poisson regression was used to calculate prevalence ratios (PR) with 95% confidence intervals (CI).Results: Of 157 patients, 19 (12.10%) tested AFB-positive. Among positive cases, AFB (1+) accounted for 52.63%, AFB (2+) for 21.05%, and AFB (3+) for 26.32%. Factors significantly associated with AFB positivity included: urban residence (PR = 3.16; 95% CI: 1.35–7.37; p = 0.018), hypertension (PR = 3.22; 95% CI: 1.27–8.19; p = 0.041), diabetes mellitus (PR = 4.75; 95% CI: 2.15–10.50; p = 0.001), alcohol consumption (PR = 3.14; 95% CI: 1.37–7.19; p = 0.005), regular alcohol use (PR = 5.52; 95% CI: 2.30–13.24; p < 0.001), cigarette smoking (PR = 3.26; 95% CI: 1.44–7.37; p = 0.007), and heavy smoking (PR = 5.27; 95% CI: 1.85–14.98; p = 0.002). No significant association was found between AFB positivity and age, sex, occupation, BMI, or tuberculosis history.Conclusion: The AFB-positive rate in the Infectious Disease Department was 12.10%. Diabetes mellitus, hypertension, alcohol use, and smoking were significant risk factors. Early AFB screening in high-risk patients is warranted.
Keywords: AFB, tuberculosis, inpatients, Infectious Disease Department, Tra Vinh.